2020
DOI: 10.22201/fpsi.20074719e.2020.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Inventario IPIP-NEO: Estabilidad y Validez de Estructura Interna, Convergente y Concurrente en Muestras Argentinas

Abstract: Las principales herramientas de evaluación de la personalidad se construyeron a partir de las bases teóricas del modelo de los Cinco Factores. Particularmente, en Argentina, el IPIP-NEO es uno de los instrumentos, basados en este modelo, que presenta resultados satisfactorios en los estudios de consistencia interna (confiabilidad) y de validez mediante evidencia de estructura interna (análisis factorial exploratorio). El objetivo de este trabajo fue aportar nuevos estudios psicométricos a la escala utilizando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…By age, OM scores are highest in the youngest group in our study (<49 years), in line with the findings of authors such as [49,50,55], and decrease significantly with increasing age [81][82][83][84], until a critical point of decline at the age of 51-61 years, in which more cognitive than emotional traits may predominate [85], and interest in the new decreases, the mind becomes more conservative and seeks more security, to increase later, between 62 and 70 years of age, a stage in which the mind becomes more curious again, open to experience and new intellectual challenges, curious and flexible. This should be taken into account in the development of a university education that considers the peculiarities derived from age, making the most of the potential of the younger generations in Openness, motivating older and more conservative students towards more OM, and highlighting the potential of the older students in Intellect, based on their greater life experience, and as a complement to the lesser life experience of the younger students.…”
Section: Discussion Conclusion and Prospectivesupporting
confidence: 93%
See 3 more Smart Citations
“…By age, OM scores are highest in the youngest group in our study (<49 years), in line with the findings of authors such as [49,50,55], and decrease significantly with increasing age [81][82][83][84], until a critical point of decline at the age of 51-61 years, in which more cognitive than emotional traits may predominate [85], and interest in the new decreases, the mind becomes more conservative and seeks more security, to increase later, between 62 and 70 years of age, a stage in which the mind becomes more curious again, open to experience and new intellectual challenges, curious and flexible. This should be taken into account in the development of a university education that considers the peculiarities derived from age, making the most of the potential of the younger generations in Openness, motivating older and more conservative students towards more OM, and highlighting the potential of the older students in Intellect, based on their greater life experience, and as a complement to the lesser life experience of the younger students.…”
Section: Discussion Conclusion and Prospectivesupporting
confidence: 93%
“…Authors such as [47,62] found significant differences in favour of older students (>25 years) compared to younger ones (<25 years), with a small effect size (d = 0.255). In some facets of OM, such as ideas and values, those over 50 years old obtained the highest scores [55]. In contrast, studies with large populations and different cultures have concluded that OM occurs mainly in younger people [50,55], with a small effect size (d of 0.443 and 0.23, respectively).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The variables measured were: Extraversion (4 items), Neuroticism (5 items), Agreeableness (4 items), Conscientiousness (6 items) and Openness to experience (4 items). The instrument was also used in other personality research [39], [40].…”
Section: Instrumentsmentioning
confidence: 99%